An Analysis of Internship Students’ Anxiety in Teaching English - Sartika Sartika; Arniati Arniati (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This research is about an analysis of internship students anxiety int eaching English. This research was conducted at STKIP Paracendekia NW Sumbawa. The purpose of this research is formulated;(1) to find out the anxiety level that internship English students in teaching English, (2) to describe the influencing factors of internship students anxiety in teaching English. There search design uses mix methods. The subjects of this study were of sixth semester students at STKIP Paracendekia NW Sumbawa. Data collection was carried out using questionnaires, interview, and documentation. The results of the study showed that students had low and medium level of anxiety. This research also shows the factors that cause students anxiety in teaching English such as: lack of proficiency, lack of preparation of teaching materials, teaching performance, lack of class management, lack of self-confidence, expectations of tutor, and difficult to adaptation. This research expected to help for student, readers and future researcher can use the results of this study references, especially regarding the anxiety of English teaching internship.